Advantages of Broad-Spectrum Influenza mRNA Vaccines and Their Impact on Pulmonary Influenza - Ziqi Cheng; Junfeng Ma; Chenyan Zhao (Vaccines)
Influenza poses a significant global health challenge due to its rapid mutation and antigenic variability, which often leads to seasonal epidemics and frequent outbreaks. Traditional vaccines struggle to offer comprehensive protection because of mismatches with circulating viral strains. The development of a broad-spectrum vaccine is therefore crucial. This paper explores the potential of mRNA vaccine technology to address these challenges by providing a swift, adaptable, and broad protective response against evolving influenza strains. We detail the mechanisms of antigenic variation in influenza viruses and discuss the rapid design and production, enhanced immunogenicity, encoding of multiple antigens, and safety and stability of mRNA vaccines compared to traditional methods. By leveraging these advantages, mRNA vaccines represent a revolutionary approach in influenza prevention, potentially offering broad-spectrum protection and significantly improving global influenza management and response strategies.